Subject-specific pedagogy development training for Chemistry teachers in collaboration with ASEAN STEAM GROUP - Sri Mulyani; Elfi Susanti VH; Sri Retno Dwi Ariani; Muhammad Hizbul Wathon (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Many secondary school teachers are interested in implementing STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning but still need assistance to plan their lessons through the development of SSP (Subject-Specific Pedagogy). STEAM is a learning approach aimed at helping students apply the primary content, practice it in everyday life, and have the skills required in the 21st century. Hence, the Chemistry Education Study Program Society Service Team of UNS, in collaboration with ASEAN STEAM researchers, aimed to improve the abilities of secondary school teachers in developing SSP for STEAM-based learning through this training. This training method was carried out hybrid. The activity began with a STEAM presentation and a workshop the next day. A pretest and post-test were given before and after training. A supervision of making SSP was carried out the following day for two weeks. The participants who worked on five SSP pretest and post-test questions showed a significant result increase in the average score of 0.6—based on a questionnaire filled out by 27 participants, 48.1% and 44.4%, respectively, stated that they had gained complete and very completely new knowledge and skills regarding the implementation of STEAM. As an evaluation, participants also provided suggestions for increasing training and mentoring time when training participants apply the training results at school.